La participación del episcopado colombiano en las negociaciones con la insurgencia: orígenes y debates (1982-1990). (2011)
This paper analyses the most representative academic works about the participation of the Colombian Bishops Conference in negotiations with insurgent groups during the eighties; focusing on their perspective about their vision of peace. In that sense; this paper analyses how the Colombian clergy adapted to the national reality their perspective of peace; identifying the main debates and the wide variety of answers; focusing on two main issues: the relevance of establishing a relationship between the need to address social issues with the overcoming of violence and the participation of bishops and priests in the talks with the insurgency. As a result of these discussions; the Colombian Catholic Church gained greater unity in action on peace and conflict.